Organic Carbon Storage and Dynamics as Affected by the Adoption of Irrigation in a Cultivated Calcareous Mediterranean Soil - Antón, Rodrigo; Derrien, Delphine; Urmeneta, Henar; van der Heijden, Gregory; Enrique, Alberto; Virto, Iñigo (Frontiers in Soil Science, 2022)
Irrigation is in the spotlight of land-use planning in semi-arid and sub-humid regions. It can be a promising practice to promote soil organic C storage (SOC), although it may also involve an increase in soil GHG emissions. Assessing the impact of its adoption on SOC storage is crucial to better understand its potential role in terms of agricultural sustainability and climate policies. In this study, we measured and modelled the changes in soil organic C storage and dynamics in the tilled soil layer (0-30 cm) of an experimental field on a calcareous soil with two different crops (maize, a C4 plant, and wheat, a C3 plant), cultivated with and without irrigation for seven years. We hypothesized that changes in SOC storage occur when introducing irrigation and/or different crops in an agrosystem, and that they would be related to changes in the incorporation of crop residues, their partitioning between the labile and the stable fraction, and C losses by mineralization. Our results validated theses hypotheses only partially. Over the 7-year study period, irrigation significantly increased total (TOC) and sand-size (50-2000 m) particulate organic C (POC50-2000) stocks in the tilled layer (0-30 cm): +7.1% TOC and +12.1% POC50-2000 for maize, and +7.0% and 12.3% for wheat. A parallel two-pool SOC model based on TOC and POC50-2000 fractions and the C3-C4 plant shift allowed understanding that the observed changes in SOC storage were most likely related to an increase in C inputs from crop residues, and to a more efficient incorporation of these residues with irrigation. The mean residence time of SOC in the two modelled pools did not allow to support our hypothesis of changes in SOC mineralization with irrigation. The limitations of SOC fractionation, which implied that some labile fractions might have been lost from POC50-2000 and recovered in the fraction identified as slow-turning, together with the interaction of the carbonate-rich mineral phase of this soil can explain at least partially this observation. We conclude that irrigation can contribute to effectively increase SOC storage in the mid-term, but its effect might be dependent upon the type of crops and soil.